Evaluation of the economics of desalination by integrating greenhouse gas emission costs: An empirical application for Chile. (April 2019) - Molinos-Senante, María; González, Diego
Abstract: Desalinated water is an alternative and feasible water source that can help solve water scarcity problems. However, most desalination plants are operated using fossil fuels, which contribute to greenhouse gas (GHG) emissions. To face the problem of climate change, many countries are developing policies that promote renewable energy for electricity production. These policies might impact desalination costs. This paper proposes a methodology to evaluate the economics of desalination by integrating investment costs, operational and maintenance costs, and GHG emissions costs. This method will enable us to determine the impact of renewable energy polices on desalination costs. The empirical application was developed for Chile, a country with a promising future in renewable energy, and revealed that the full costs of desalinated water decrease by approximately 22% when the current electricity production mix is changed to predominantly renewable energy production. Moreover, this application illustrated the relevance of adopting a carbon tax to motivate the switch to renewable energy. This study demonstrates that the adoption of renewable energy policies involves a notable synergy with water issues. Highlights: Methodological proposal to estimate desalination costs integrating external costs. Evaluation of the impact of renewable energy polices on desalination costs. The adoption of renewable energy policies involves synergy with water issues.